Adolescents' Physical Activity in Education Systems Varying in the Number of Weekly Physical Education Lessons - Groffik, Dorota; Mitáš, Josef; Jakubec, Lukáš; Svozil, Zbyněk; Frömel, Karel (Research quarterly for exercise and sport, 2020)
Purpose: School physical activity (SPA) is a significant component of daily PA. We investigated differences in PA between boys and girls in two differing education systems-Poland and the Czech Republic-which have four and two physical education lessons (PELs) per week, respectively. Method: This project was conducted from 2012-2016 at 17 Polish and 23 Czech secondary schools (N = 921; mean age = 16.2 ± 0.7 years). ActiTrainer accelerometers were used to monitor participants' PA and heart rate during school days. Weekly PA was measured using pedometers. Subjective levels of weekly PA were self-reported on the International Physical Activity Questionnaire-long form. Results: The Polish education system enabled adolescents to meet the recommendations for moderate-to-vigorous PA more likely than did the Czech system. SPA also represented a higher portion of daily PA in the Polish (vs. Czech system); however, the differences in total daily step count between Polish and Czech adolescents were non-significant. SPA accounted for 30-37% of the daily PA (as measured by step count) of Polish girls (23-30% of Czech girls) and 28-39% of Polish boys (25-37% of Czech boys). Conclusions: Participation in PELs was associated with a higher rate of meeting SPA recommendations in both countries. Compared with the Czech Republic, more PELs in the Polish education system was associated with increased daily vigorous PA and a greater portion of SPA in daily PA. Differences in overall daily and weekly moderate-to-vigorous PA between Polish and Czech adolescents were non-significant.
Keywords: nositelná elektronika; Physical Education and Training; Male; zpráva o sobě; Healthy Lifestyle; Adolescent; Poland; Česká republika; Heart Rate; Monitoring; akcelerometrie; mužské pohlaví; zdravý životní styl; srdeční frekvence; Exercise; mladiství; Czech Republic; Time Factors; tělesná výchova; lidé; ženské pohlaví; Humans; Wearable Electronic Devices; Self Report; časové faktory; Accelerometry; Female; cvičení; Polsko; IPAQ-LF; healthy school habits